ANALISIS KOMPOSISI RULE OF THIRDS PADA AKUN INSTAGRAM @INALUM UNTUK MENINGKATKAN DAYA TARIK VISUAL EDISI FEBRUARI 2025 - Anindita Sadira, Rafa; David Rizar Nugroho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is entitled "Analysis of the Rule of Thirds Composition on the Instagram Account @INALUM to Increase Visual Appeal, February 2025 Edition", which aims to analyze the effectiveness of the implementation of the Rule of Thirds in improving the aesthetics and engagement of visual content on the company's social media. In an increasingly competitive digital era, visual appeal is a crucial factor in building effective communication with the audience. INALUM as an aluminum industry company uses Instagram as the main platform to convey company information, sustainability programs, and industry education to the public. This study uses a qualitative descriptive analysis method, by observing and evaluating the visual composition of the Instagram upload @INALUM. The results of the study show that the implementation of the Rule of Thirds is able to improve visual balance, direct the audience's focus to the main elements in the image, and create a more professional and attractive appearance. However, several challenges were found in its implementation, such as the inconsistency of the Rule of Thirds in text-based content, the need for training for the social media team, and the need to adjust to the company's visual identity. Based on the analysis results, it is recommended that INALUM develop standard design guidelines, conduct creative team training, and adapt the Rule of Thirds technique with the company's branding elements to remain consistent and effective in attracting audience attention. With the right strategy, the implementation of the Rule of Thirds can be a solution to improve the quality of visual content, strengthen INALUM's digital identity, and encourage higher engagement on social media.